How to spot Ugly Black Ducklings: the next competitive frontiers in scholarly publishing. Issue 4 (1st October 2013) - FROEHLICH, Peter
ABSTRACT: This paper reviews events of SSP 2013 and AAUP 2013 within the context of Nassim Nicholas Taleb's notions of Black Swans (unexpected game changers) to anticipate the formation of competitive arenas (i.e. new models and revenue streams) for scholarly communications. It examines Tim O'Reilly's keynote address at SSP 2013, the advice of Michael Schrage from the opening Plenary at AAUP 2013, and Tim Sullivan's discussion of Harvard Business Publication's use of a topical blog network as new publishing platform to access global digital communications networks. The essay extrapolates from the case studies presented to overlay the strategies of successful practitioner presses and the advice of sought‐after business consultants on the work of academic houses, to imagine the next competitive frontier(s) in scholarly publishing.